Evaluation of Texture of Packhams Pears - Guiné, Raquel (2013)
The textural parameters, together with appearance and flavor, are sensory attributes of great importance for the product to be accepted by the consumer. The objective of the present study was the evaluation of the textural attributes of Packhams pears in the fresh state, after drying in a chamber with forced convection at 50 ºC, lyophilized and re-hydrated. In texture analysis it was used the method of Texture Profile Analysis (TPA). The parameters analyzed were hardness, cohesiveness, adhesiveness, elasticity and chewiness. From the results obtained is possible to see that the drying operation greatly affected some textural properties of the pears, so that the hardness diminished very much with drying, for both drying methods.